An analysis of commit-time requirements for ontology views - Ahmad, Mohammad Nazir; M. Colomb, Robert; Sadiq, Shazia (Penerbit UTM Press, 2008)
One of the major uses of the ontology IS to support interoperation of information systems which that ontology is a result ofInterlocking Institutional Worlds (IWs). In this context, typically, application development in collaborative setting requires users to commit particular applications to an ontology. In such environment, the user employs an ontology server to identify ontology objects the user considers essential to commit the application. Since there are many users, therefore their different perspectives will require server to generate views on the ontologies. The ontology views are fairly established in ontology modularization research but in the context of IWs we argue that the problems may be distinct. Therefore, this paper is to define several ontology views problems and subsequently propose some sort of requirements for ontology views with respect to IWs. Furthermore, we discuss our analysis in the sense of ontology modularization approaches and argue that our problems make differences thus require another new approach to solve it.